ダイ49ジ ニホン ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2008 - 吉見, 英史; ヨシミ, ヒデシ; 石井, 洋子; イシイ, ヒロコ; 望月, 隆史; モチヅキ, タカシ; 岩渕, 真海; イワブチ, マサミ; 水野, 太治; ミズノ, タイジ; Yoshimi, Hideshi; Ishii, Hiroko; et al. (2013)
P(論文) この報告は第49次日本南極地域観測隊気象部門が,2008年2月1日から2009年1月27日までの越冬期間中に昭和基地において行った気象観測結果をまとめたものである.観測方法・測器・統計方法などは第48次隊とほぼ同様である. 越冬期間中,特記される気象現象として,次のものが挙げられる. 1)9月1日,175 hPaから上層のすべての気圧面で,9月としての最低気温の極値を更新した. 2)地上気象観測において,10月の平均気温は-17.5°Cと低く,これまでの平均値として最も低い極値(2007年までの記録は1991年10月の-16.1°C)を更新した. 3)昭和基地上空のオゾン全量は,8月下旬から11月下旬までオゾンホールの目安となる220 m atm-cmをほぼ継続的に下回った.特に9月中旬から10月中旬にかけてオゾン全量が非常に少なく,10月16日には2008年でも最小値である140 m atm-cmを記録した (2007年までの最小値は2006年10月17日の114 m atm-cm). This report describes the result of meteorological observations at Syowa Station by the Meteorological Observation Team of the 49th Japanese Antarctic Research Expedition (JARE-49) during the period 1 February 2008 to 27 January 2009. The observation methods, instruments, and statistical methods used by the JARE-49 team are nearly the same as those used by the JARE-48 observation team. Remarkable weather phenomena observed during the period of JARE-49 are as follows. 1) On 1 September 2008, the record minimum temperature for September was observed in the upper atmosphere (pressure greater than 175 hPa). 2) The monthly mean temperature at Syowa Station during October 2008 was -17.5°C; this is the lowest monthly mean October temperature recorded at Syowa Station. 3) The total ozone over Syowa Station was less than or equal to 220 m atm-cm during the period from late August to late November, and was close to minimum levels during the period from mid-September to mid-October. The lowest total ozone in 2008, recorded on 16 October 2008, was 140 m atm-cm. departmental bulletin paper